Selecting sequence numbers. - Tomlinson, Raymond S. (Computer communication review.)
A characteristic of almost all communication protocols is the use of unique numbers to identify individual pieces of data. These identifiers permit error control through acknowledgement and retransmission techniques. Usually successive pieces of data are identified with sequential numbers and the identifiers are thus called sequence numbers.This paper discusses techniques for selecting and synchronizing sequence numbers such that no errors will occur if certain network characteristics can be bounded and if adequate data error detection measures are taken. The discussion specifically focuses on the protocol described by Cerf and Kahn (1), but the ideas are applicable to other similar protocols.